Representasi banjir dalam film “love at first flood” di thailand (Jurnal Kajian Media, 2019)
The phenomenon of flood disaster that flooded the city in Thailand for 40 days, the flood resulted in looses that not only property but also the increasing number of deaths every day. A traumatized state, director Poj Arnon made a flood film that almost entirely flooded the setting in Thailand (Love at First Flood 2012). This qualitative research by the semi-analytical method of Christian Metz or semiology analysis explains how the Love at First Flood film present dystopia and utopia repression that explains the reinforcement of messages that make up a meaning. The eight-step Metz mapping is used to unpack distinctive film structures, Through metaphorical masters and catharchic languages containing the repression of dystopia and utopia as a sign, the meaning expressed in the film’s messages is: (1) A support, (2) Awareness for mutual help, (3) Respects for fellow human beings.Keywords: Semiotics film; Flood; Dystopia and utopia representation.